Aerial view of exposition
Caption on card: "You could see, in the distance, surrounded by trees, the strange Porte Monumentale... near it the Alexander III Bridge and the new Grand and Petit palaces for the art exhibtis... and, crowded in on the near side of the Seine, the foreign pavilions..."